Nonmonotonic Hydration Behavior of Bovine Serum Albumin in Alcohol/Water Binary Mixtures: A Terahertz Spectroscopic Investigation. Issue 7 (1st March 2017) - Das, Dipak Kumar; Das Mahanta, Debasish; Mitra, Rajib Kumar
Abstract: We report the experimental observation of nonmonotonic changes in the collective hydration of bovine serum albumin (BSA) in the presence of alcohols of varying carbon‐chain lengths, that is, ethanol, 2‐propanol, and tert ‐butyl alcohol (TBA), by using terahertz (THz) time domain spectroscopy. We measured the THz absorption coefficient ( α ) of the protein solutions, and it was observed that α fluctuated periodically as a function of alcohol concentration at a fixed protein concentration. For a fixed alcohol concentration, an increase in the protein concentration resulted in nonmonotonic changes in α ; thus, it first decreased rapidly and then increased, which was followed by a shallow decrease. An alcohol‐induced α helix to random coil transition of the protein secondary structure was revealed by circular dichroism spectroscopy measurements, and the effect was most prominent in TBA. The anomalous change in the hydration was found to be a delicate balance between the various interactions present in the three‐component system. Abstract : Stay hydrated ! The collective hydration of bovine serum albumin (BSA) in the presence of alcohols with varying carbon‐chain lengths is studied by using terahertz time‐domain spectroscopy. We observe that the terahertz absorption coefficient ( α ) fluctuates periodically as a function of alcohol concentration at a fixed protein concentration, whereas nonmonotonic changes occurs in α for a fixed alcohol concentration with increasing protein concentrations.